Identification of QTLs Linked to Phenological and Morphological Traits in RILs Population of Horsegram (Macrotyloma uniflorum) - Katoch, Megha; Mane, Rushikesh Sanjay; Chahota, Rakesh Kumar (Frontiers in Genetics, 2022)
Horsegram [Macrotyloma uniflorum (Lam.) Verdc.] is an important legume but understudied in terms of its genetic improvement. Genetic information on various phenological and morphological traits may help in the utilization of new genes for breeding in horsegram and thus affect agronomic practices and crop yield. A total of 162 recombinant inbred lines derived from intraspecific crosses between HPKM249 × HPK4 was used to construct a genetic linkage map and to identify quantitative trait loci (QTLs) associated with phenological and morphological traits. Of the total 2011 molecular markers, which were screened on parental lines for polymorphism survey, 493 markers were found to be polymorphic and used for genotyping of recombinant inbred line population. Out of 493 polymorphic markers, 295 were mapped on ten linkage groups at LOD 3.5 spanning a total distance of 1,541.7 cM with an average distance between markers of 5.20 cM. Phenotypic data of two years at two different locations were used to identify QTLs by composite interval mapping A total of four QTLs (LOD ≥2.5) for phenological traits (days to 50% flowering, reproductive period and days to maturity) and seven QTLs (LOD ≥2.5) for morphological traits (plant height, primary branches and secondary branches) were detected across different environments. The phenotypic variation explained by QTLs ranged from 6.36 to 47.53%. The present study will help to augment scanty genomic information in this orphan crop that would provide genomics tools to breeders for its genetic enhancement through molecular-assisted selection.